EFFICACY OF NEW INSECTICIDES GENERATION IN THE CONTROL OF TOMATO LEAF MINER (Tuta absoluta Meyrick) (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
The tomato leaf miner (Tuta absoluta) is a pest that causes significant damage to tomato production in Bosnia and Herzegovina. According to previous research, the inadequate application of older generation insecticides in the control of tomato leaf miner has led to a series of harmful consequences, such as increased resistance of the pest, reduction of the natural enemies population and an increase in pesticide residues in the agricultural products and in the environment. The aim of this work was to examine the efficacy of the newer insecticides generation in controlling of tomato leaf miner in greenhouse production in southern Bosnia and Herzegovina. Testing the efficacy of insecticides was carried out on tomato plants (Matias hybrid) in greenhouses in the localities of Višići, Gabela and Klepci. The effectiveness was tested on the following variants of insecticides: Indoxacarb, Emamectin benzoate, Methoxyfenozide, Lufenuron, Chlorantraniliprole, Azadirachtin, Spinosad and the combination of Abamectin + Lufenuron. Based on the number of live larvae in the mines, according to Abbott, the efficiency values of the applied insecticide variants were calculated. The combination of insecticides based on the active substances Abamectin and Lufenuron showed the highest percentage of efficiency (53.52%). The insecticide based on the active substance Spinosad showed the lowest percentage of efficiency. Lower efficiency values of the majority tested insecticides are probably a consequence of their specific mechanism of action, physical-chemical properties and environmental conditions in which they were applied.